2007
DOI: 10.1007/s11894-007-0063-7
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny and developmental physiology of gastric acid secretion

Abstract: The production of acid by the stomach is a tightly controlled physiological process that involves neural and hormonal mechanisms and the input of several epithelial cell types. The past several years have seen significant advances in our understanding of the molecular ontogenesis of the stomach and the factors controlling stomach innervation, as well as the differentiation of gastric epithelial cell lineages and their respective hormones/factors that influence acid production. The programmed development of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…It is known that stomach full development during the fetal period is up to the 14 th or 15 th gestational week and that 27-week-old preterm infants are capable of gastric pH <4.0 on the first day of life. However, in the first 48 hours after birth, the literature indicates that the pH may be higher due to low gastric acid secretion, lack of food or the presence of amniotic fluid in the stomach ( 15 - 17 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that stomach full development during the fetal period is up to the 14 th or 15 th gestational week and that 27-week-old preterm infants are capable of gastric pH <4.0 on the first day of life. However, in the first 48 hours after birth, the literature indicates that the pH may be higher due to low gastric acid secretion, lack of food or the presence of amniotic fluid in the stomach ( 15 - 17 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Lebenthal, E by 15 weeks. [29][30][31] This variation in the time of appearance in different studies may be attributed to the age of the fetus studied or the different study techniques. But, the present observation clearly demonstrated that the initial development of circular layer occurred before 12 weeks of gestation and not later; the muscularis externa showed a craniocaudal pattern of development since the innermost oblique layer was seen at 12 weeks in cardiac region and at 14 weeks in the body region.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, term infants have low acid output initially, which becomes normal within several days. 73 regulation of postnatal nutritional adaptation is schematically represented in Figure 11 -6. Human milk is the optimal nutritional source of calcium during the first year of life. 74 Human milk also contributes trophic factors that aid digestive system maturation and immunoglobulins that reduce the risk of infection.…”
Section: Function Across the Life Spanmentioning
confidence: 99%